LEI DE RESPONSABILIDADE FISCAL: a institucionalização do Estado brasileiro em defesa do capital financeiro - Costa Filho, Samuel (2014)
The objective of this work is to reveal the economic logic and the interests and conflicts contained in the legal-institutional instrument of the Fiscal Responsibility Law (FRL), in its adoption and enforcement of rules in the modern capitalist State budget in Brazil, in the concept of balanced budget in view of the theories of orthodoxy; according to which, under capitalism, state intervention in the economy is an unnecessary, harmful, disruptive activity to the economic optimum. To achieve this goal, the work sits in bibliographical and dialectical analysis in order to understand the capitalist state, its laws, its measures and its institutionalization in the current globalized financial historical-institutional context in which the priority has been the setting tax to ensure the timely payment of state obligations to creditors on government debt. The methodology and design of this thesis sought to cover the difficult issue of the contemporary state under the rule of finance capital. It starts in the realization of the importance of understanding the FRL for the correct analysis of the performance of the State in the Brazilian economy. Accordingly, the study, in total contrast with the academic, instrumental and ideological importance of the mainstream theories about the FRL, seeks to highlight that logic in defense of finance capital, shrouded in analyzes of legal, accounting or economic issues, restricted to area of public finances, concluding that the FRL is treated as a breakthrough in the institutionalization of the tax rules of the State, as a matter of good public administration only, being restricted to tax and financial issues.